Biological heterogeneity in Parkinson’s disease: implications for MRI-based patient stratification - Marta M. Pokotylo; Norbert Brüggemann; Jannik Prasuhn (npj Parkinson's Disease, 2026)
Abstract Parkinson’s disease is increasingly recognized as a heterogeneous syndrome characterized by diverse pathological processes and clinical manifestations. Here, we propose a multidimensional framework to assess this heterogeneity, with each dimension potentially captured using advanced magnetic resonance imaging techniques. The framework comprises dominant pathological processes, spatial distribution patterns of pathology across brain regions, propagation architecture, temporal dynamics of disease progression, co-pathology burden, and system response and resilience mechanisms.